2017
DOI: 10.20849/ijsn.v3i1.365
|View full text |Cite
|
Sign up to set email alerts
|

A Need Assessment for Faculty Development in Baccalaureate Nursing Programs in Pakistan

Abstract: Objective: A needs assessment was undertaken for faculty development needs of nurse educators teaching in baccalaureate nursing education programs across Pakistan.Methodology: The survey instrument was developed by the researcher in consultation with an advisory committee. It contained 25 items that reflected the demographic profile of the participants and another 98 statements on a 5 point Likert type scale to assess faculty development. Data collection was done across twenty schools of nursing.Results: The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…First, another study conducted in Pakistan reported the desire of nurse educators to learn about teaching and learning strategies in faculty development activities. 9 Second, another study in the USA reported that participants want to know how to teach and assess their students. 25 Finally, a study in Karachi noted that instructional skills, including planning, designing, teaching, and evaluating, were evaluated as the priority choice for competency development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, another study conducted in Pakistan reported the desire of nurse educators to learn about teaching and learning strategies in faculty development activities. 9 Second, another study in the USA reported that participants want to know how to teach and assess their students. 25 Finally, a study in Karachi noted that instructional skills, including planning, designing, teaching, and evaluating, were evaluated as the priority choice for competency development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study's findings were consistent with many previous studies regarding the desire of nurse educators to learn about teaching and learning strategies. First, another study conducted in Pakistan reported the desire of nurse educators to learn about teaching and learning strategies in faculty development activities 9 . Second, another study in the USA reported that participants want to know how to teach and assess their students 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations